WAYS TO IMPROVE THE EFFICIENCY OF INVESTMENT OF INSURANCE RESERVES IN RUSSIA - Oleg S. Bobkov; Irina P. Kurochkina (Статистика и экономика)
The article is devoted to the analysis of preconditionsof increase in a share of investments of the Russian insurance companies in Russia’s GDP. It deals with the features of improving the investment managing methodsof their insurance reserves. The causes of enterprises weaken investment activity of insurance are formulated,where a low return on investment insurance companiesis the main. There are main reasons of investment insurance’s increase: the modernization of Russian Legacy on the one hand and improvement of analysisinvestment of insurance reserves efﬁ ciency methods by introduction of the additional analytical parameterson the other hand